Librarians of the World Unite? Possibilities and realities from Florida, USA. (1st October 2010) - James F. Tracy; Maris L. Hayashi
Abstract : This paper examines the perspectives of academic librarians in Florida's public universities concerning library work and advocacy for workplace rights by professional organisations and the statewide faculty union. An online survey was used to gather responses to closed and open-ended questions from 58 librarians. These data are presented alongside discussions addressing professionalism in library work, the history of US library professional organisations and workplace issues, and Florida's faculty union. The results suggest that, in terms of broader organisation around workplace issues, academic librarians in Florida are stuck between managerial expectations of professional practice and a faculty union slow to understand the significance of librarianship.